2014
DOI: 10.5153/sro.3187
|View full text |Cite
|
Sign up to set email alerts
|

Researching the Intangible: A Qualitative Phenomenological Study of the Everyday Practices of Belonging

Abstract: How can the intangible aspects of everyday life be uncovered? A phenomenological approach has its origins in the everyday but also allows everything to be questioned. In studying belonging a phenomenological approach supported by a variety of qualitative methods produced a wealth of ‘insider’ information that could have been missed using more traditional methods. The research was based around multi-generational family groups as a family narrative focuses on relations between different family members over the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
(42 reference statements)
0
24
0
4
Order By: Relevance
“…Understanding the lifeworlds of others may be best achieved through ethnographic observation and participation, yet this is not always practical and may not capture participants’ meaning (Bennett, 2014). Other sources of data may, therefore, be better suited to understanding lived experience and its meaning (Bennett, 2013; Plunkett, Leipert, & Ray, 2013). These include photographs, logbooks, and interviews (Lopez & Willis, 2004; Sandelowski, 1995).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the lifeworlds of others may be best achieved through ethnographic observation and participation, yet this is not always practical and may not capture participants’ meaning (Bennett, 2014). Other sources of data may, therefore, be better suited to understanding lived experience and its meaning (Bennett, 2013; Plunkett, Leipert, & Ray, 2013). These include photographs, logbooks, and interviews (Lopez & Willis, 2004; Sandelowski, 1995).…”
Section: The Studymentioning
confidence: 99%
“…Within research into residents’ experiences of their neighborhoods and/or communities, PEI has also been used to explore living in underprivileged areas (Kasemets, 2014), racial constructions (Leddy-Owen, 2014), and the demolition of a residential area characterized by segregation (Altenberger & Robertson, 2013). Researchers have also used pictures, often in combination with diaries and interviews, to discuss the meaning participants ascribe to particular places (Bennett, 2013; Harper, 2004; Latham, 2003; Moore et al, 2008). For instance, Latham (2003) used photographic and written diaries to explore the ways urban places, including a particular hospitality strip in downtown Auckland, “become” through the interweaving of the lives of the individuals who use them.…”
Section: Introductionmentioning
confidence: 99%
“…Belonging in family relations is thus not a state to be accomplished once and for all, but rather an ongoing achievement through dynamic practices (May, 2011). As Bennett (2014) argues, belonging is often an unconscious part of everyday life, perhaps first considered when one does not feel it. Children placed in foster care experience a change (sometimes several) in their everyday family setting, and as they move between different potential ‘belonging settings’ their senses of belonging can become conscious.…”
Section: Introductionmentioning
confidence: 99%
“…Children placed in foster care experience a change (sometimes several) in their everyday family setting, and as they move between different potential ‘belonging settings’ their senses of belonging can become conscious. Belonging then becomes an explicit process of revealing if and how they ‘feel comfortable, at home, at place’ (Bennett, 2014: 1) in their respective family settings. In childhood studies, the concept of belonging has recently been applied to migration research, exploring children with a migration background and their sense of belonging (see Bak and von Brömssen, 2010; Den Besten, 2010; McGovern and Devine, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these consequences is the missed opportunity to deepen understanding of the circumstances and expressions that characterize experiences of family support. This is not unique to the study of families of LGBTQ+ people; indeed, Bennett observed () that “there is more academic literature relating to not belonging than to belonging” (p. 1). However, given broad recognition of the importance of family acceptance and support for queer youth (Shilo & Savaya, ), there is a particular urgency to understanding the conditions that both facilitate and complicate belonging in this context.…”
mentioning
confidence: 99%